Seasonal changes in vitamin D-effective UVB availability in Europe and associations with population serum 25-hydroxyvitamin D - O'Neill, Colette M; Kazantzidis, Andreas; Ryan, Mary J; Barber, Niamh; Sempos, Christopher T.; Durazo-Arvizu, Ramon A.; Jorde, Rolf; Grimnes, Guri; Eiriksdottir, Gudny; Gudnason, Vilmundur; Cotch, Mary Frances; Kiely, Mairead; et al. (Nutrients, 2016)
Source: doi:10.3390/nu8090533 Low vitamin D status is common in Europe. The major source of vitamin D in humans is ultraviolet B (UVB)-induced dermal synthesis of cholecalciferol, whereas food sources are believed to play a lesser role. Our objectives were to assess UVB availability (Jm−2) across several European locations ranging from 35° N to 69° N, and compare these UVB data with representative population serum 25-hydroxyvitamin D (25(OH)D) data from Ireland (51–54° N), Iceland (64° N) and Norway (69° N), as exemplars. Vitamin D-effective UVB availability was modelled for nine European countries/regions using a validated UV irradiance model. Standardized serum 25(OH)D data was accessed from the EC-funded ODIN project. The results showed that UVB availability decreased with increasing latitude (from 35° N to 69° N), while all locations exhibited significant seasonal variation in UVB. The UVB data suggested that the duration of vitamin D winters ranged from none (at 35° N) to eight months (at 69° N). The large seasonal fluctuations in serum 25(OH)D in Irish adults was much dampened in Norwegian and Icelandic adults, despite considerably lower UVB availability at these northern latitudes but with much higher vitamin D intakes. In conclusion, increasing the vitamin D intake can ameliorate the impact of low UVB availability on serum 25(OH)D status in Europe